1998
DOI: 10.1175/1520-0469(1998)055<1354:etgmso>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Gross Moist Stability of the Tropical Atmosphere*

Abstract: Recent theoretical studies have indicated that large-scale circulation in deep convective regions evolves subject to an overall static stability-termed the gross moist stability-that takes into account both dry static stability and moist convective effects. The gross moist stability has been explicitly defined for a continuously stratified atmosphere under convective quasi-equilibrium constraints. A subsidiary quantity-the gross moisture stratification-measures the overall effectiveness in producing precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 30 publications
6
97
0
1
Order By: Relevance
“…Previous studies estimated that deep convection discharges column MSE by vertical advection at a rate of approximately 20 % of precipitation in warm pool regions and approximately 14 % over the Maritime Continent (Yu et al 1998). Recent MSE analysis by Sobel et al (2014) for the DYNAMO MJO events found a similar rate of MSE discharge by vertical advection during peak MJO activitybetween 10 % and 20 % of precipitation (their Figs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies estimated that deep convection discharges column MSE by vertical advection at a rate of approximately 20 % of precipitation in warm pool regions and approximately 14 % over the Maritime Continent (Yu et al 1998). Recent MSE analysis by Sobel et al (2014) for the DYNAMO MJO events found a similar rate of MSE discharge by vertical advection during peak MJO activitybetween 10 % and 20 % of precipitation (their Figs.…”
Section: Discussionmentioning
confidence: 97%
“…A highly idealized theoretical analysis of Yu et al (1998) suggested that the export of column MSE by vertical motions associated with deep convection occurs at a rate of approximately 20 % of precipitation over the west Pacific warm pool and southeast Indian Ocean and at a rate of approximately 14 % of precipitation near the Maritime Continent. In more recent findings, Sobel et al (2014) showed vertical advection discharges column MSE at a rate of 10 % -20 % of precipitation at the peak of the CINDY/ DYNAMO (i.e., Cooperative Indian Ocean Experiments on Intraseasonal Variability in the Year 2011; Dynamics of the MJO) field campaign (Yokoi et al 2014;Moum et al 2013).…”
Section: Brief Background On Wishe and Moisture Mode Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the divergent component of the AET can often be related to the ITCZ. Since MSE typically increases with altitude, AET generally diverges where mean vertical motions in the tropics are upward (Yu et al 1998)-potentially with the exception of a narrow region in the mid-Pacific (Back and Bretherton 2006). We therefore define the zonally varying EFE as the latitude where the meridional component of the divergent columnintegrated MSE flux both vanishes and has a positive meridional gradient.…”
Section: A First-order Approximationmentioning
confidence: 99%
“…The warm and cold ENSO composites for the moist stability in the model atmosphere, based on a definition analogous to that of Neelin and Held (1987), are also computed. Weaker moist stability over the central Pacific (not shown) is found during El Niñ o years, which might be conducive to the slower MJO propagation during warm events (see, e.g., Wang and Li 1994;Yu et al 1998). Another possible mechanism for the change of the MJO phase speed is the advection by the time mean flow, as the mean upper-level zonal wind is decreased during warm ENSO events in the same central Pacific region in the November-March period (not shown).…”
Section: B Observational Datamentioning
confidence: 99%